Strengthening Beef Cattle Farming through Agribusiness Subsystem Integration: SWOT and System Analysis in Muara Badak District - Dede Aprylasari; Anindyasari, Dinar; Indana, Khoiru; Yunita, Annisa; Najih, Riyan Riyadlun (CV. Komunitas Dunia Peternakan, 2025)
This study aims to analyze the strategy of strengthening beef cattle farming through an integrated agribusiness subsystem approach at the Sebatur Tunggal Farmer Group in Muara Badak District, Kutai Kartanegara Regency. The background of this study is based on the importance of developing an integrated agribusiness system to increase the productivity and competitiveness of smallholder livestock farming, especially in the face of challenges such as feed availability, market access, and institutional and technological support. This study uses a qualitative descriptive method with a case study approach, where data is collected through observation, in-depth interviews with members of farmer groups and related parties, and documentation studies. The results of the study indicate that each agribusiness subsystem—starting from the input subsystem (upstream), cultivation subsystem (on-farm), processing and marketing subsystem (downstream), to supporting subsystems such as institutions, capital, and technology—is still running partially and has not been optimally integrated. The main problems identified include limited access to quality feed, low application of efficient cultivation technology, limitations in processing livestock products, and weak marketing and partnership networks. In addition, the institutional capacity of farmer groups to manage businesses collectively still needs to be strengthened. The conclusion of this study states that the strategy for strengthening beef cattle farming businesses needs to be focused on developing an integrated agribusiness system with support from training, extension, access to inputs and markets, and cross-sector collaboration. The main recommendation is the need for policy interventions that encourage synergy between subsystems and empower farmers through a participatory and sustainable approach to create a resilient and competitive community farm.